Application of Liquid Organic Fertilizer (LOF) from Bamboo Leaves on the Growth and Production of Green Mustard Plants (Brassica juncea L.) - Puspita Sari Sitorus; Badrul Ainy Dalimunthe; Dini Hariyati Adam; Novilda Elizabeth Mustamu (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
Green mustard (Brassica juncea L.) is a popular vegetable among Indonesians across all social classes. It has high nutritional value and is rich in vitamins A, B, C, E, and K. This study aims to determine the effect of liquid organic fertilizer (LOF) on the vegetative growth of green mustard (Brassica juncea L.). The research employed analysis of variance (ANOVA) for data analysis, using a Completely Randomized Design (CRD). If significant differences were found, further testing was conducted using the smallest real difference test. The results showed that treatment with 90 ml/L of LOF derived from bamboo leaf waste consistently produced the best growth results over three weeks of observation, with plant height reaching 21.00 cm, the number of leaves reaching 9.67, and the largest leaf width measuring 6.33 cm. These data indicate that applying 90 ml/l of bamboo leaf waste LOF significantly improves plant morphology and health compared to other treatments, suggesting that this treatment can be an effective strategy to increase the productivity of green mustard.